PENGARUH BUDAYA INOVATIF DAN GAYA KEPEMIMPINAN SUPORTIF TERHADAP KOMITMEN ORGANISASI (Studi Pada Karyawan PT. BPR Guna Daya Boyolali) - Pratama, Candra Agil; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2018)
PT. BPR Guna Daya Boyolali is one of the best Rural Banks in Boyolali. The results of this research interview by the chief of staff human resourch management, obtained data related to growth and reduction of the number of employees who resign, will affect the organization commitment of employee organization in PT. BPR Guna Daya Boyolali.This research aims to analyze the influence of innovative culture and supportive style of leadership towards organizational commitment. Study on employees at PT. BPR Guna Daya Boyolali.The number of sample used in this research were 55 respondents. Sample were chosen using probability sampling technique with simple random sampling method. The analytical method used in this research is Multiple Linear Regression Analysis where previouslytested the validity and reliability, then performed classical assumption that includes Normality Test, Multicollinearity Test, and Heteroskedastisitas Test.The result of this research found that innovative culture has a positive and significant impact on organizational commitment. Supportive leadership styles have a positive and significant impact on organizational commitment.